THE INTEGRAL ROLE OF LITERATURE IN PRIMARY EDUCATION: A COMPREHENSIVE REVIEW - Nodira Sherboeva; Mamatqulova Nodira (International Scientific and Current Research Conferences, 2024)
Literature plays a pivotal role in primary education, offering young learners a gateway to imagination, empathy, critical thinking, and language development. This paper examines the multifaceted benefits of integrating literature into primary education, highlighting its influence on cognitive, social, and emotional development. Through a comprehensive review of existing literature and empirical studies, this article underscores the importance of incorporating diverse literary works in the curriculum to foster holistic learning experiences and nurture lifelong readers.